Student Feedback Systems: Developing a Web-Based Solution for Efficient Complaint Processing at Faculty of Information Technology Tarumanagara University - Phratama, Owen Maytrio; Handhayani, Teny; Perdana, Novario Jaya (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
The collection of student feedback, encompassing aspirations, and complaints, serves as a cornerstone in improving the quality of education and fostering institutional responsiveness in higher education. However, many universities, including Tarumanagara University, especially the Faculty of Information Technology still rely on manual processes for submitting these concerns, necessitating face-to-face interactions with faculty administrative personnel. This traditional approach often results in inefficiencies, including delayed responses and difficulty tracking complaints. This research addresses these issues by proposing the development of a web-based application designed to centralize and streamline the processing of student complaints and aspirations. Utilizing the waterfall model as the development methodology, the application is developed using ASP.NET with C# and SQL Server to ensure robust performance and data management. The outcomes of this initiative demonstrate significant improvements in both time efficiency and resource allocation for handling student feedback within the Faculty of Information Technology at Tarumanagara University. By implementing this web-based solution, the faculty aims to foster a more effective and responsive feedback mechanism that enhances student engagement and satisfaction.